2007
DOI: 10.1111/j.1439-0442.2007.00908.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Temporal Aspects of ACTH Secretion: Stimulatory Actions of Corticotropin‐Releasing Hormone and Vasopressin in Cattle

Abstract: The objective of the present study was to evaluate the temporal aspects associated with corticotropin-releasing hormone (CRH) and vasopressin (VP) stimulated bovine adrenocorticotropic hormone (ACTH) secretion in vitro and in vivo. For the in vitro studies, bovine anterior pituitary glands were enzymatically dispersed to establish primary cultures. On day 5 of culture, cells were challenged for 3 h with medium alone (Control) or various combinations and concentrations of bovine CRH (bCRH) and VP. Both CRH and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…A similar increase in circulating cortisol following CRH has been reported previously in other studies using exogenous CRH challenges in Jersey, Brahman and Holstein-Friesian cattle. [28][29][30] Previous researchers have suggested that greater baseline and cortisol responses to stressors in cattle may be an indication of down-regulation of glucocorticoid receptors and other receptors regulating cellular immunity located in the hypothalamus. [31][32][33] Similar to our findings, newly weaned Angus heifers tended to have greater circulating cortisol concentrations than bulls following an endotoxin challenge.…”
Section: Resultsmentioning
confidence: 99%
“…A similar increase in circulating cortisol following CRH has been reported previously in other studies using exogenous CRH challenges in Jersey, Brahman and Holstein-Friesian cattle. [28][29][30] Previous researchers have suggested that greater baseline and cortisol responses to stressors in cattle may be an indication of down-regulation of glucocorticoid receptors and other receptors regulating cellular immunity located in the hypothalamus. [31][32][33] Similar to our findings, newly weaned Angus heifers tended to have greater circulating cortisol concentrations than bulls following an endotoxin challenge.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, both in vitro and in vivo data demonstrated that while AVP acutely activates the bovine pituitaryadrenal axis, CRF-induced ACTH secretion is slower in onset but of longer duration [65].…”
Section: Adrenocorticotropic Hormone Releasementioning
confidence: 98%
“…Plasma was subsequently aspirated and stored at −20°C until assayed. Cortisol concentrations were determined in a single RIA from duplicate samples using a single antibody RIA procedure (Carroll et al, 2006) and used: rabbit anticortisol antiserum (Pantex, Div. of Bio-Analysis Inc., Santa Monica, CA, Cat.…”
Section: Blood Sampling and Analysismentioning
confidence: 99%